The Role of Artificial Intelligence in Human Capital Management: A Review at PT. Pos Indonesia - Sora Baltasar; Tonggo Marbun (International Institute for Advanced Science & Technology (IIAST), 2025)
PT. Pos Indonesia is committed to overcoming digital era challenges by implementing strategic transformations, particularly through the adoption of Artificial Intelligence (AI). AI plays a key role in enhancing operational efficiency, service quality, and revenue growth. It optimizes logistics, accelerates courier services, and personalizes customer interactions, contributing to an 18.64% increase in business revenue in 2023, reaching Rp 5,479,12 billion. This growth is driven by AI based automation in supply chain management and customer data analysis. The goal of this research is to explore how PT. Pos Indonesia can address AI implementation gaps and optimize its use to gain sustainable competitive advantages in operations and Human Capital Management (HCM). It also aims to provide strategies for developing human resource management and enhancing efficiency through AI. In HCM, AI improves recruitment, training, and employee development, supporting skill analysis, personalized training, and performance evaluation. This transformation aligns with AKHLAK values, fostering collaboration and adaptability while supporting remote work models for O-Rangers and postal agents via realtime monitoring. AI also helps PT. Pos Indonesia adapt to the evolving e-commerce industry by optimizing delivery routes, predicting demand, and empowering digital platforms like Pospay. Automation improves cost efficiency and customer service, strengthening PT. Pos Indonesia position in the digital logistics and courier services market. Through AI integration in HCM and operations, PT. Pos Indonesia enhances profitability and establishes sustainable competitive advantages, positioning itself as a model for technology driven business innovation in Indonesia logistics and financial sectors.